Biological water contamination in some cattle production fields of Argentina subjected to runoff and erosion - Chagas, Celio Ignacio (2014)
Grain production has displaced livestock to marginal lands in most of the productive regions in Argentina since 1990. In the fertile Rolling Pampa region, extensive cattle production has been concentrated in lowlands subjected to flooding, salt excess, erosion and sedimentation processes but also in some feedlots recently located in sloping arable lands prone to soil erosion. We studied the concentration of microbiological contamination indicators in runoff water and sediments accumulated in depressions along the tributary network from these lands devoted to cattle production. The aims of this work were: (i) to gather a reliable set of data from different monitoring periods and scales, (ii) to search for simple and sensible variables to be used as indicators for surface water quality advising purposes and (iii) to corroborate previous biological contamination conceptual models for this region. Concentration of pollution indicators in these ponds was related to mean stocking rates from nearby fields and proved to depend significantly on the accumulated water and sediments. Viable mesophiles and total coliforms were found mainly attached to large sediments rather than in the runoff water phase. Seasonal sampling showed that the time period between the last significant runoff event and each sampling date regarding enterococci proved to be a sensible variable for predicting contamination. Enterococci concentration tended to increase gradually until the next extraordinary runoff event washed away contaminants. The mentioned relationship may be useful for designing early warning surface water contamination programs regarding enterococci dynamics and other related microbial pollutants as well.